Why is neuron modeling of particular philosophical interest? - Polak, Paweł (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2022)
This review article discusses Andrzej Bielecki’s book Models of Neurons and Perceptrons: Selected Problems and Challenges, as published by Springer International Publishing. This work exemplifies “philosophy in science” by adopting a broad, multidisciplinary perspective for the issues related to the simulation of neurons and neural networks, and the author has addressed many of the important philosophical assumptions that are entangled in this area of modeling. Bielecki also raises several important methodological issues about modeling. This book is recommended for any philosophers who wish to learn more about the current state of neural modeling and find inspiration for a deeper philosophical reflection on the subject.
Keywords: neuron modeling; sub-neuron modeling; computational modeling; analog computation; philosophy in science; philosophy of biology; philosophy of computing